Pengaruh Ratio-Ratio Keuangan CAR, LDR, NIM, BOPO, NPL Terhadap ROA - harun, usman (Universitas Sam Ratulangi, 2016)
The (soundness) level of Bank Umum can be assessed by several indicators. One of the main indicators that become base of evaluation is the financial report that concerned. Based on thefinancial report, will be calculated numbers of financial ratios commonly used as a rating of Commercial Bank (Bank Umum). Financial report analysis can help the businesses agents, isit government and other financial report users to assess the financial condition of the Bank. The results showed that the has no effect on ROA. LDR influence significantly on ROA. NIMno effect on ROA. BOPO influence significantly on ROA. The influence of NPL to ROA insignificant. These finding support the results of research conducted by Usman (2003) whereNPL did not influence significantly on earnings changes.Keywords: CAR, LDR, NIM, ROA, NPL, Banks, Financial Ratios